A phenomenological criterion for an optical assessment of PE-HD fracture surfaces obtained from FNCT. (February 2021) - Schilling, Markus; Niebergall, Ute; Marschall, Niklas; Alig, Ingo; Böhning, Martin
Abstract: The full-notch creep test (FNCT) is a common test method to evaluate the environmental stress cracking (ESC) behavior of high-density polyethylene (PE-HD), e.g. for container materials. The test procedure as specified in ISO 16770 provides a comparative measure of the resistance against ESC using the time to failure of PE-HD specimens under constant mechanical load in a well-defined liquid test environment. Since the craze-crack damage mechanism underlying the ESC phenomenon is associated with brittle failure, the occurrence of a predominantly brittle fracture surface is a prerequisite to consider an FNCT measurement as representative for ESC, i.e. a time to failure dominated by craze-crack propagation. The craze-crack propagation continuously reduces the effective residual cross-sectional area of the specimen during the test, which results in a corresponding increase of the effective mechanical stress. Thus, a transition to ductile shear deformation is inevitable at later stages of the test, leading usually to a pronounced central ligament. Therefore, an optical evaluation of FNCT fracture surfaces concerning their brittleness is essential. An enhanced imaging analysis of FNCT fracture surfaces enables a detailed assessment of craze-crack propagation during ESC. In this study, laser scanning microscopy (LSM) was employed to evaluate whether FNCT fracture surfaces are representative with respect to craze-crack propagation and ESC. Based on LSM height data, a phenomenological criterion is proposed to assess the validity of distinct FNCT measurements. This criterion is supposed to facilitate a quick evaluation of FNCT results in practical routine testing. Its applicability is verified on a sample basis for seven different commercial PE-HD container materials. Graphical abstract: Image 1 Highlights: Environmental stress cracking (ESC) was characterized by Full Notch Creep Test (FNCT). Fracture surfaces were analyzed using Laser Scanning Microscopy (LSM). Signatures of brittle crack propagation and ductile shear deformation were identified. Using numerical height data from LSM a phenomenological criterion is proposed. The criterion allows to classify the fracture.